Facts and Fiction in Oil Market Modeling - Lutz Kilian (Center for Economic Studies and ifo Institute (CESifo), 2019)
Baumeister and Hamilton (2019a) assert that every critique of their work on oil markets by Kilian and Zhou (2019a) is without merit. In addition, they make the case that key aspects of the economic and econometric analysis in the widely used oil market model of Kilian and Murphy (2014) and its precursors are incorrect. Their critiques are also directed at other researchers who have worked in this area and, more generally, extend to research using structural VAR models outside of energy economics. The purpose of this paper is to help the reader understand what the real issues are in this debate. The focus is not only on correcting important misunderstandings in the recent literature, but on the substantive and methodological insights generated by this exchange, which are of broader interest to applied researchers.
Keywords: Q43; Q41; C36; C52; 330; oil supply elasticity; oil demand elasticity; IV estimation; structural VAR; Bayesian inference; oil price; global real activity